Data turn: LA SVOLTA DIGITALE DELLE INFRASTRUTTURE DI SORVEGLIANZA: DATI SENSIBILI MIGRAZIONI E PAESI TERZI SICURI - Buffa, Matteo (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2025)
This contribution examines the intersection between new technologies (AI, Internet of Things, biometric and sensitive data) and the governance of migration in Europe, in light of recent legal reforms and case law. Through a critical analysis of the so-called data turn, the paper explores the legal and technological mechanisms employed in the externalization of migration control, administrative detention, and refugee status determination. The article reflects on the evolving boundaries of international protection and the growing role of digital infrastructures in surveillance and containment of migration flows, highlighting risks to human rights, privacy, and the declarative nature of refugee status.